INOVASI NAZHIR DALAM PENGELOLAAN WAKAF DIGITAL SEBAGAI STRATEGI KEBERLANJUTAN EKONOMI UMAT DI ERA PANDEMI - Faujiah, Ani; Imron (ICO EDUSHA, 2022)
Innovation in the management of digital waqf by nazhir plays a crucial role in maintaining the sustainability of the community's economy, particularly during the COVID-19 pandemic. Digital transformation allows waqf to be managed more transparently, efficiently, and inclusively, thus reaching a larger portion of the community. Through digital platforms, people can more easily participate in channeling waqf funds, while nazhir can manage waqf assets more effectively. However, there are several challenges to address, such as low digital literacy among nazhir, limited regulations supporting digitalization, and public trust in the security of digital transactions. This research aims to analyze the impact of digital waqf on the community's economy and identify innovations implemented by nazhir in managing digital waqf. Through a qualitative approach with literature studies, the research finds that although technologies like blockchain and Islamic crowdfunding offer great potential to enhance transparency and efficiency, regulatory challenges and public trust need to be addressed. This study recommends digital training for nazhir, strengthening regulations, and developing safer technologies to maximize the potential of digital waqf as a strategy for sustainable community economic empowerment. Keywords: Digital Waqf, Nazhir Innovation and Economic Empowerment.